Movie Recommendation System Using Item Based Collaborative Filtering (International Journal of Innovative Research in Computer Science & Technology, 2020)
In today's digital world where there is an  endless variety of content consumed such as books, videos,  articles, Films, etc., finding material of one's choice has  become an infallible task. Digital content on the other hand  Providers want to engage more and more users in their  service for maximum time. Where is it the recommender  system comes into picture where content providers advise  users by content User choice in this paper we have proposed  a movie recommendation system .Purpose of movie  recommendation system aims to provide users with accurate movie recommendations. Usually basic  recommendation system to make recommendations  consider one of the following factors; User preference  known as content based Filtering or the preference of  similar users known as collaborative filtering. To create a  stable and accurate recommender system will use of content  based filtering.
Keywords: Movies, Recommendation system; CBF Content-based filtering; CF- Collaborative filtering